Effectiveness of filler injection after thread lifting procedure of severe midface volume loss: a preliminary study - Girgin, Aysegul (Aesthetic Medicine, 2025)
Objective: There are many methods used to rejuvenate the skin and improve its quality. In our study, effectiveness of filler injection after thread lifting procedure of severe midface volume loss was evaluated. Methods: In the study, there were two groups of patients treated with PLA/CL alone (n=5) and a combination of PLA/CL and hyaluronic acid filler (n=5). Treatment covers a period of 1 month. Differences before and after treatment were evaluated with the help of photography and a statistical program. Results: These results were evaluated by both the patient and the doctor. When the survey data were evaluated, only 27% improvement was observed in the PLLA group and 45% improvement in the combined treatment group. Combined treatment was also found to be more effective in evaluating skin moisture, colour, fine lines, jawline, mouth lines, and skin elasticity. Conclusion: Results shows that PLA/CL and hyaluronic acid filler application is more effective than only PLA/CL application.